A Focused Exploratory Study on Understanding the Role of Healthcare Quality Professionals in the Middle East - Shaik Mohiuddin (Patient Safety and Quality Improvement Journal, 2024)
Introduction:Healthcare quality personnel have contributed to and prepared organizations to meet various quality and safety challenges. With extensive roles, clarity of their work and responsibilities is needed. However, their role still needs to be clarified.  This focused study aimed to explore the scope of quality personnel within the Middle East through a representative group of professionals in the "Gulf Corporation Council (GCC) Quality Professionals Forum. Materials and Methods: Following the literature review, a suitable questionnaire was identified using the National Association for Healthcare Quality (NAHQ) domains for the group survey. The survey was conducted on April 5, 2022, at a workshop. In addition, the participants were discussed to clarify the roles and responsibilities of quality professionals. Results: The findings of this study are significant, revealing that patient safety and health data analytics are the top two areas within the scope of quality personnel, with scores of 90% and 83.3%, respectively. In contrast, involvement in population health (40%) and influencing culture (56.2%) were considered the least involved areas. The results provide insights for optimizing workforce competencies and enhancing healthcare contributions. Conclusion:The study has identified varying job responsibilities for quality professionals in the region, highlighting the minimal emphasis on public health. It underscores the necessity for collaborative efforts among all stakeholders to establish standardized guidelines for the scope of practice for quality personnel. Further investigation and extension of this study to a larger sample size is required, especially in the Middle East region, to assess the subject in more noteworthy profundity.